Work vs. family and marital satisfaction among Malaysian Chinese dual-earner couples: an actor-partner interdependence model - Leong, Mei San; Juhari, Rumaya (South-West University Neofit Rilski, Department of Psychology, 2021)
Work-family conflict is frequently studied because they are the two main life domains in a person’s life. The present study examines how work-family conflict influenced marital satisfaction among Malaysian Chinese dual-earner couples using a dyadic approach. Results from the Actor-Partner Interdependence Model (APIM) indicated that work-family conflict (work-to-family and family-to-work) were associated with a lower level of marital satisfaction. Work-family conflict has a significant negative impact on marital satisfaction for both husbands and wives (actor effect). However, no significant results were found for the partner effect. Both actor and partner effects were reported and discussed. The present findings provide empirical evidence on the spillover and crossover effects of work-family conflict on marital satisfaction and add to the literature by utilizing advanced data analysis technique, APIM by collecting dyadic data. The implications of the findings were discussed as well as the suggestions for future research.